Translational frontiers: insight from lymphatics in skin regeneration - Jiang, Yujia; Perez-Moreno, Mirna (Frontiers in Physiology, 2024)
The remarkable regenerative ability of the skin, governed by complex molecular mechanisms, offers profound insights into the skin repair processes and the pathogenesis of various dermatological conditions. This understanding, derived from studies in human skin and various model systems, has not only deepened our knowledge of skin regeneration but also facilitated the development of skin substitutes in clinical practice. Recent research highlights the crucial role of lymphatic vessels in skin regeneration. Traditionally associated with fluid dynamics and immune modulation, these vessels are now recognized for interacting with skin stem cells and coordinating regeneration. This Mini Review provides an overview of recent advancements in basic and translational research related to skin regeneration, focusing on the dynamic interplay between lymphatic vessels and skin biology. Key highlights include the critical role of stem cell-lymphatic vessel crosstalk in orchestrating skin regeneration, emerging translational approaches, and their implications for skin diseases. Additionally, the review identifies research gaps and proposes potential future directions, underscoring the significance of this rapidly evolving research arena.